The stability of electricity prices: estimation and inference of the Lyapunov exponents - Mikael Bask; Tung Liu; Anna Widerberg (Bank of Finland, 2006)
The aim of this paper is to illustrate how the stability of a stochastic dynamic system is measured using the Lyapunov exponents. Specifically, we use a feedforward neural network to estimate these exponents as well as asymptotic results for this estimator to test for unstable (chaotic) dynamics.The data set used is spot electricity prices from the Nordic power exchange market.Nord Pool, and the dynamic system that generates these prices appears to be chaotic in one case.
URN:NBN:fi:bof-20140807603
Keywords: C12; C14; C22; 330; feedforward neural network; Nord Pool; Lyapunov exponents; spot electricity prices; stochastic dynamic system